Future Intelligent Systems and Networks 2019 - de Pablos Heredero, Carmen (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In this Special Issue, we present current developments and future directions of future intelligent systems and networks. This is the second Special Issue regarding the future of the Internet. This subject remains of interest for firms applying technological possibilities to promote more innovative business models. This Special Issue widens the application of intelligent systems and networks to firms so that they can evolve to more innovative models. The five contributions highlight useful applications, business models, or innovative practices based on intelligent systems and networks. We hope our findings become an inspiration for firms operating in various industries.